AFRICAN IDENTITIES: A NARRATIVE OF INTERSECTIONALITY AND COHESION - Théophile , Munyangeyo (International Journal of Allied Research in Sociology and Anthropology, 2023)
This article explores the issue of tribal and ethnic identities in Africa and their impact on social tensions, political intolerance, and violence. Through a discourse analysis of the works of two African novelists, Eugène Nzamboung and Dominique M'Fouillou, the article demonstrates how these writers construct identities in their narratives as constructive "alterity" rather than negative sources of conflict. Using ontological and anthropological perspectives, the article examines the representation of key concepts, such as identities, existence, being, becoming, and the representation of historical and social reality. The article argues for a reconceptualization and reclamation of African identity, emphasizing the need to transcend divisive ethnic and tribal affiliations in favor of a shared identity in order to overcome conflict and promote social cohesion